PARADIGMA NEGARA DALAM DISKURSUS PARTAI POLITIK ISLAM DI TANAH AIR - Mohammad Masrur (At-Taqaddum, 2013)
Ascerttaining concept of the state is one of the central issues in the history of political idea, as it not apart from Islamic political thought. At least there are three paradigms of the relationship both religion and state in the Islamic political thought. First, religion and state are inseparable; second, religion and state are associated symbiotically. And third, secularism is a paradigm that proposes the separation of religion and state.Nurcholish Majid (1939-2005) can be regarded as leading Islamic intellectuals in Indonesia who seek the moral-theological keystone on how can Islamic moral teachings are grounded as capable of giving meaning to the process of political change that took place in political dynamic of the nation. One of key issues in this discourse is how Islamic associate with the state of how the Islamic concept of state.